Pentingnya Motivasi Dari Diri Sendiri Pada Peserta Didik Dalam Pembelajaran Pendidikan Agama Hindu - Ekayanti, Putu Yulia; Temon Astawa, I Nyoman (Cetta: Jurnal Ilmu Pendidikan, 2022)
Intrinsic motivation plays a crucial role in Hindu Religious Education learning as it affects the extent to which learners can absorb and apply religious teachings in their lives. Learning processes that rely solely on external factors such as assessment, punishment, or reward may not be effective in shaping a deep understanding and acceptance of religious values. This study aims at the importance of self-motivation in learners in learning Hinduism education. The study adopts a qualitative approach, utilizing literature study or desk study as the main technique in information gathering. Understanding and applying Hinduism learning concepts in depth improves the quality and practice of teachings in learners' lives. A holistic and conducive approach to the learning environment, including teaching methods, curriculum and teacher-student interactions, is essential to foster students' intrinsic motivation. Teacher and family collaboration is important in developing this motivation. Integration of disciplines in Hinduism learning, such as history, art, and philosophy, provides a broader and deeper understanding. Individualized education is also important, allowing students to pursue their interests. Intrinsic motivation, involving intention, determination, and sustained effort, is crucial to achieving well-being in Hinduism education.